INDONESIAN STUDENTS’ PERCEPTIONS OF ENGLISH MEDIUM INSTRUCTION - Puspitasari, Titik; Ishak, Cita Nuary (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
There has been an increasing trend in Indonesian higher education to run international programs. As a result, English for Medium Instruction (EMI) has started to be implemented in several departments at Indonesian universities. To successfully implement EMI classes, lecturers and students do play significant roles. This paper aims to gain insights into students’ perceptions of EMI and the challenges they faced in terms of understanding the subject content. Using convenience sampling, 35 undergraduate students of the International Psychology Program (IPP) at a private university in Indonesia were selected as the participants of the study. We used an explanatory sequential design using questionnaires and interviews as the instruments to collect the data. The findings revealed that the majority of the students have a positive perception of the implementation of EMI in their classes. However, its implementation also posed some challenges such as difficulties in comprehending lectures and the lack of ability in using English to conduct classroom discussions. The findings suggested the need for training before EMI courses that help students increase their English proficiency level as well as lecturers to improve their EMI pedagogic competence.